History of Islam Abu Bakar as-Siddiq (R.A) - Aziz, Maulvi Abdul (Riyadh : Darussalam, 2012)
"History of Islam: Abu Bakr as-Siddiq (R.A)" by Maulvi Abdul Aziz is the inaugural volume in Darussalam's "History of Islam" series. Tailored for Muslim youth, the book offers an authentic and engaging account of Abu Bakr as-Siddiq (R.A), the first Caliph of Islam, highlighting his pivotal role in the early Muslim community.
Keywords: History : Islam; Abu Bakr as-Siddiq : Darsussalam